2023
DOI: 10.1063/5.0138674
|View full text |Cite
|
Sign up to set email alerts
|

The Auger spectrum of benzene

Abstract: We present an ab initio computational study of the Auger electron spectrum of benzene. Auger electron spectroscopy exploits the Auger-Meitner effect and, al- though it is established as an analytic technique, the theoretical modeling of molecular Auger spectra from first principles remains challenging. Here, we use coupled- cluster and equation-of-motion coupled-cluster theory combined with two approaches to describe the decaying nature of core-ionized states: (i) Feshbach-Fano resonance theory and (ii) the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 117 publications
3
34
0
Order By: Relevance
“…We previously demonstrated that total and partial Auger decay widths can be extracted from CBF-EOMIP-CCSD wave functions of core-ionized states. [67][68][69] The decay is represented in these wave functions by 2h1p-excitations that fill the core hole. The resulting configurations give rise to the metastable character and are responsible for convergence problems when methods are used that do not treat the decay properly.…”
Section: Determination Of Auger Decay Widths With Complex-variable Me...mentioning
confidence: 99%
See 4 more Smart Citations
“…We previously demonstrated that total and partial Auger decay widths can be extracted from CBF-EOMIP-CCSD wave functions of core-ionized states. [67][68][69] The decay is represented in these wave functions by 2h1p-excitations that fill the core hole. The resulting configurations give rise to the metastable character and are responsible for convergence problems when methods are used that do not treat the decay properly.…”
Section: Determination Of Auger Decay Widths With Complex-variable Me...mentioning
confidence: 99%
“…However, we recently showed that, even though the two approaches describe Auger decay in different ways, CBF-CCSD and Fano-EOM-CCSD agree well with each other about the Auger spectrum of benzene. 69…”
Section: Determination Of Auger Decay Widths With the Feshbach-fano M...mentioning
confidence: 99%
See 3 more Smart Citations